2013
DOI: 10.1038/cdd.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional fine-tuning of microRNA-223 levels directs lineage choice of human hematopoietic progenitors

Abstract: MicroRNAs (miRNAs) regulate cell proliferation, differentiation and death during development and postnatal life. The expression level of mature miRNAs results from complex molecular mechanisms, including the transcriptional regulation of their genes. MiR-223 is a hematopoietic-specific miRNA participating in regulatory signaling networks involving lineage-specific transcription factors (TFs). However, the transcriptional mechanisms governing its expression levels and its functional role in lineage fate decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 49 publications
5
54
1
Order By: Relevance
“…In line with previously published data [14,25,27], we confirm that miR-223 promotes myeloid/ granulocytic differentiation. We also found in vitro and in vivo evidence that miR-223 increases erythroid and monocytic differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previously published data [14,25,27], we confirm that miR-223 promotes myeloid/ granulocytic differentiation. We also found in vitro and in vivo evidence that miR-223 increases erythroid and monocytic differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…The complex miR-223 phenotypes encountered in the different AML mouse models can hardly be reconciled with the published functions of miR-223 in human hematopoiesis, which mainly relate to its role in promoting myeloid differentiation [25,27]. We therefore set out to further define the role of miR-223 in human primary hematopoietic cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, myeloid balanced hematopoiesis was achieved by overexpression of miR- Notably, a recent study revealed HPCs differentiating into granulocytes and monocytes presented with 10-fold and 3-fold up-regulation of miR-223, respectively. In contrast, HPCs giving rise to erythrocytes maintained low levels of miR-223 (82). Lastly, HSCs undergoing either erythroid or megakaryocytic differentiation were found with upregulated expression of miR-146b (83).…”
Section: Hematopoietic Stem Cells and Leukemic Stem Cellsmentioning
confidence: 70%
“…The replacement of NFI-A by C/EBPα and the ensuing granulocytic differentiation are further reinforced by a feedback loop regulation of miR-223, which represses NFI-A. Interestingly, a separate study using CD34 + human hematopoietic progenitor cells (HPCs) showed that the promoter of miR-223 is bound by different transcription factors in a lineage-dependent manner, in which miR-223 is up-regulated during granulopoiesis and monocytic differentiation but remains low during erythropoiesis [89]. Using transfection of synthetic oligonucleotides (mimics and inhibitors), overexpression of miR-223 in CD34 + HPCs promoted granulopoiesis, whereas silencing of it facilitated the erythroid and monocytic pathways.…”
Section: 0 Mirnas and Stem Cells Propertiesmentioning
confidence: 99%